Upaya Pemerintah Kabupaten Banyuwangi Menurunkan Stunting (SDG 2.2) - Lapian, Jonathan Edward; Harahap, Insan Harapan (Journal of Entrepreneurship, Management and Industry (JEMI), 2023)
In light of the determination to address Sustainable Development Goals, the Indonesian government has established the vision of “Indonesia Emas 2045”, with human development and the ability of science and technology to play a significant role in increasing health and society’s quality of life. To achieve this vision, Indonesia has to solve the challenges in public welfare including stunting as a chronicle condition that affects child growth and development. These challenges related to Zero Hunger of SDG 2 which aims to end poverty and access to safe and nutritious food to be met by all levels of society. In order to gain a comprehensive analysis of the efforts of the Indonesian government to reduce stunting rates, this study has undertaken the limitations of research within the Banyuwangi Regency as one of the top levels of stunting rates in national prevalence in 2018 with an improvement trend of 8% in the following year. This study accessed data from the officials’ site of the Banyuwangi government and the results of previous research to subsequently subjected to descriptive analysis method with a qualitative approach. The findings of this research indicate the significant accomplishment of Banyuwangi Regency’s government in solving the stunting problems within the regency as the result of a commitment to achieving Zero Stunting as the answer to SDG 2.